The Role of Intestinal Microbiota in Regulating the Metabolism of Bile Acids Is Conserved Across Vertebrates - Xiong, Fan; Chen, Sijia; Jakovlić, Ivan; Li, Wenxiang; Li, Ming; Zou, Hong; Wang, Guitang; Wu, Shangong (Frontiers in Microbiology, 2022)
In mammals, bile acid (BA) concentrations are regulated largely by the gut microbiota, and a study has shown that some metabolic responses to the gut microbiota are conserved between zebrafish and mice. However, it remains unknown whether the influence of specific intestinal microbes on BA metabolism is conserved between higher and lower vertebrates (i.e. mammals and fish). In the present study, Citrobacter freundii GC01 isolated from the grass carp (Ctenopharyngodon idella) intestine was supplemented to the fish and mice feed. We found the changes in the bile acid profile, especially significant changes in secondary BAs in both grass carp and mice fed on C. freundii. Also, lipid metabolism was significantly affected by C. freundii. Analysis of liver transcriptome sequencing data and validation by RT-qPCR revealed that the CYP7A1 gene was significantly up-regulated in both grass carp and mice. In addition, the overexpression of HNF4B from grass carp resulted in a significant increase in the expression level of CYP7A1. Generally, our results suggest that the metabolism of BAs by intestinal microbiota is conserved across vertebrates. Furthermore, specific intestinal bacteria may regulate the bile salt synthesis through CYP7A1 and that HNF4B might be an important regulator of BA metabolism in fish.